The Effectiveness of Teaching Self-Management to Students with Autism Spectrum Disorder on Their Self-Management, On-Task and Task Completion Skills - Akın Gönen; Yahya Çıkılı (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Özel Eğitim Dergisi)
Introduction: Self-management strategies (SMS) consist of antecedent cue regulation, self-monitoring, self-instruction, self-evaluation, or self-reinforcement strategies. Students with autism spectrum disorder (ASD) can use these strategies especially in their daily life skills, academic skills, or in environments that require social skills.Method: In this study, the effect of self-management (SM) teaching on the acquisition and maintenance of SMS by students with ASD was examined. It was also aimed to determine how students acquire and maintain the behaviors of on-task and task completion by using strategies, and to what extent they generalize the strategies and target behaviors to different people/environments. The study was conducted using multiple probe design with probe conditions across subjects, one of the single-subject research models.Findings: The findings of the study showed that SM teaching was effective in helping students with ASD acquire SMS, and that students who used the strategies continued to use the strategies after the intervention. In addition, it was determined that students who used the SMS consisting of antecedent cue regulation, self-monitoring, self-evaluation, and self-reinforcement increased their on-task and task completion levels, maintained the gains after the intervention and generalized them to different people and environments. Social validity findings collected from the participants showed that they were positive about the use and effects of the SMS.Discussion: There was a significant increase in students' pre-teaching and post-teaching performances regarding target behaviors. The effectiveness of SM interventions was tried to be supported by the findings of the current study and was consistent with the results of the related study.